A Gastrointestinal Stromal Tumor of the Stomach Demonstrating a Stepwise Progression from Low- to High-Grade Malignancy - Takahiko Nakajima; Tomonori Ushijima; Atsushi Kihara; Kenichiro Murata; Toshiro Sugiyama; Koichi Tsuneyama; Johji Imura; Junichi Fukushima; Hajime Horiuchi (Case Reports in Gastrointestinal Medicine)
We report a case of a gastrointestinal stromal tumor (GIST) of the stomach that demonstrated a stepwise progression from low- to high-grade malignancy. The patient had been followed for a small gastric submucosal tumor that had turned malignant after 8 years of indolence, manifested by tarry stools. The tumor was enucleated, and gastric GIST was diagnosed. The most significant histological finding was that the tumor comprised two clearly demarcated areas, one with less aggressive characteristics and the other with highly aggressive characteristics. The patient exhibited multiple liver metastases 24 months after surgery. Imatinib mesylate was not administered throughout the clinical course because it was not available for clinical use at that time. The patient followed an unfavorable clinical course and died of liver dysfunction 55 months after surgery. Autopsy was performed. By comparing the immunohistochemical profiles of primary and metastatic tumors, it was established that only the tumor cells with highly aggressive characteristics had metastasized.